The Impact of Wages, Population Growth, Investment, and Inflation on Unemployment Rates in ASEAN-5 - Mochammad Fikri Firmansyah; Gigih Pratomo (OECONOMICUS Journal of Economics, 2025)
This study aims to analyze the impact of minimum wage, population growth, foreign direct investment (FDI), and inflation on the unemployment rate in five ASEAN countries during the period 2016-2023. The data used in this research is secondary data obtained from the World Bank and the International Labour Organization, covering five ASEAN countries (Indonesia, Malaysia, Thailand, Philippines and Vietnam) over eight years. The method employed is panel data regression using a fixed effect model (FEM), with result showing that minimum wages, population growth, and inflation have a significant negative effect on the unemployment rate, while foreign direct investment (FDI) significantly has a positive effect on the unemployment rate in ASEAN from 2016-2023. These findings suggest the importance of integrated policies in managing labor market dynamics in the ASEAN region.